2012
DOI: 10.1063/1.3696971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stress state and strain rate on structural amorphization in boron carbide

Abstract: The reduced performance of B4C armor plate for impact against tungsten carbide penetrators beyond a critical velocity has been attributed in the literature to localized amorphization. However, it is unclear if this reduction in strength is a consequence of high pressure or high velocity. Despite numerous fundamental studies of B4C under indentation and impact, the roles of strain rate and pressure on amorphization have not been fully established. Toward this end, rate dependent uniaxial compressive strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 31 publications
5
74
0
Order By: Relevance
“…Several theoretical studies have shown that the strain rate dependence of the peak (failure) stress of brittle materials is strongly dependent on the characteristics of such defects . The rate dependence was also observed experimentally in many advanced ceramics, including BC …”
Section: Resultsmentioning
confidence: 70%
“…Several theoretical studies have shown that the strain rate dependence of the peak (failure) stress of brittle materials is strongly dependent on the characteristics of such defects . The rate dependence was also observed experimentally in many advanced ceramics, including BC …”
Section: Resultsmentioning
confidence: 70%
“…Ceramics are generally brittle at room temperature, however, plastic deformation of alumina, aluminum nitride, silicon carbide, boron carbide, and zirconia at extreme loading conditions, such as in high‐pressure compression, indentation, and shockwaves, has been observed . Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al . observed that plastic deformation‐induced twins were activated when a stress higher than the Hugoniot elastic limit (HEL) was reached in alumina . Extensive dislocations were observed at the impact surface of silicon carbide at pressure exceeding its HEL .…”
Section: Introductionmentioning
confidence: 99%
“…These anomalies in the high‐pressure performance of boron carbide spurred numerous investigations into the evolution of short‐range disorder in the material, often referred to as “amorphization”. Subsequent studies have also documented amorphization under Berkovich and Vickers indentations, laser shock impact, mechanical scratching, and nonhydrostatic loading in diamond anvil cell experiments . Postmortem TEM of the deformed regions revealed inhomogeneous distributions of nanoscale amorphized zones within the crystalline matrix of boron carbide …”
Section: Introductionmentioning
confidence: 93%